Market feedback: Evidence from the horse’s mouth - Goldstein, Itay; Liu, Bibo; Yang, Liyan (Journal of Financial Economics, 2026)
We surveyed all Chinese public firms in 2019 and 2022 to examine the real effects of financial markets. Over 90% of firms say they actively monitor the stock market, and the most common reasons they provide are that they learn new information from the price and that they depend on the price for financing. Focusing on the learning channel, we examine how the responses relate to firm characteristics and actions. Firms that indicate learning have characteristics that suggest greater benefit from market information. They also exhibit higher investment-to-price sensitivity. We provide results on what dimensions of information firms learn about.